FRI0027 5-aminolevulinic acid induced protoporphyrin ix formation in arthritic synovial tissues: an approach for synovial photodynamic therapy in arthritis. (1st June 2001) - Kirdaite, G; Lange, N; Busso, N; Van den Bergh, H; Kucera, P; So, A
Abstract : Background: Objectives: To determine the optimal conditions for synovial accumulation of protoporphyrin IX (PpIX) and light induced synovial cytotoxicity in arthritis in vitro and in vivo . Methods: In vitro studies: Synovial biopsies from patients with osteoarthritis (OA, n = 9), rheumatoid arthritis (RA, n = 3) and synovial tissues from mice with antigen-induced arthritis (AIA, n = 9) were incubated with different concentrations of 5-aminolevulinic acid hexyl-ester (h-ALA), a protoporphyrin IX (PpIX) precursor. Tissue PpIX content was determined by microspectrofluorometry. Following photoexcitation, the synovial tissues were evaluated by Sytox-Green fluorescence for cell death. Animal studies: h-ALA was injected intra-articularly into knee joints of mice with AIA (n = 40). Following photodynamic therapy (PDT) in vivo, joint inflammation was assessed by technetium scintigraphy and histology. Results: In human biopsies, the highest fluorescence intensity was observed after incubation with 0.5–1 mM h-ALA. Kinetic studies showed that PpIX accumulation in human tissues reached a peak at 3 h in OA and increased linearly up to 6 h in RA. Murine tissues showed highest fluorescence intensity at a concentration of 4 mM in vitro and 8 mM in vivo . By fluorescence microscopy, PpIX was localised to the synovial lining layer, endothelial cells and macrophages. Irradiation of pre-incubated tissues in vitro led to significant cell death. PDT in vivo in AIA led to a statistically significant reduction of histological parameters of joint damage in irradiated joints. Conclusion: Our findings suggest that PDT based on PpIX accumulation in the synovial membrane may be a rational basis for photodynamic synovectomy in arthritic diseases.